2018
DOI: 10.2478/folmed-2018-0016
|View full text |Cite
|
Sign up to set email alerts
|

Bulgarian Experience with Adverse Drug Reaction Reports from Patients and Consumers – Retrospective Data-base Study

Abstract: Background: Since 2012, in compliance with the changes in the European legislation, the Bulgarian Drug Agency (BDA) has been receiving adverse drug reaction (ADR) reports directly from patients as well as from healthcare professionals and marketing authorization holders (MAH). Adverse reaction reports from patients and consumers have different characteristics from those sent by healthcare professionals. Moreover, they may require specific algorithm and assessment methods in order to be informative and benefici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Our respondents mainly preferred reporting by telephone, as in other studies [25,43,54]. There were also more people who liked to report ADRs online.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Our respondents mainly preferred reporting by telephone, as in other studies [25,43,54]. There were also more people who liked to report ADRs online.…”
Section: Discussionsupporting
confidence: 50%
“…There were also more people who liked to report ADRs online. Other studies [6,25,46,54] have also showed that some people have a tendency for reporting ADRs via SMS, email, completing a paper form, online, and other reporting methods. Thus, to improve the reporting rate and satisfy the needs and choices of different people, providing a variety of ADR reporting methods and channels is needed when establishing a public ADR reporting system.…”
Section: Discussionmentioning
confidence: 97%
“…The factors linked to investments in healthcare were recorded to correlate with elevated patient engagement in adverse reactions reporting whereas the aspects of pharmacovigilance did not correspond directly to the increase in patients participation in drug-safety monitoring [ 40 ]. Easily accessible and user-friendly systems for patient reporting as well as innovative assessment algorithms have been indicated as future directions for the changes and development of pharmacovigilance [ 41 ]. L. Rolfes et al investigated the level of satisfaction with the feedback received after providing the reports, and they demonstrated that the patients expected the feedback regardless of whether it was provided as a personalized letter or an automated response that confirmed the report submission [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Drug eruptions, also known as toxidermia, are cutaneous symptoms that occur as a result of systemic drug administration. These reactions range from mild erythematous skin lesions to far more serious reactions like toxic epidermal necrosis [12]. Morbilliform or erythematous maculopapular eruptions account for around 40% of all drug eruptions.…”
Section: Discussionmentioning
confidence: 99%